(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2016)
In this paper we described and investigated deminutivy and augmentativy, which is displayed through the lens of Ukrainian language picture of the world. With the knowledge, selection and use of different nouns with specific means of Ukrainians choose in the first evaluation, connotative one, but not neutral. It is established that the creation of these derivatives affect actual linguistic factors, sociolinguistic and psycholinguistic. According to our observations, the formation of derivatives – deminutyviv and auhmentatyviv – uplyvayut following factors: linguistic, sociolinguistic and psycholinguistic. During the actual linhistychnymy understand language typological properties that affect the formation of the lexicon, namely suffixal way of creation, which actively influences the creation and deminutyviv auhmentatyviv. Sociolinguistic factor also leads to the creation of derivatives analyzed. This is facilitated by globalization, development of new technologies and the emergence of related realities, as well as the interaction between languages and between neighboring linguistic formations within society. Another factor in the creation and deminutyviv, auhmentatyviv is psycholinguistic – a way of understanding the collective knowledge of native speakers sociolinguistic conditions. Ukrainian factor due psychology. The new name, something specific and memorable increasingly attracts attention when used in broadcasting.